Zeondo dataset for Probing the limits of the phonon quasi-particle picture: Transitions between underdamped and overdamped dynamics in CsPbBr3 - Erik Fransson; Petter Rosander; Fredrik Eriksson; Magnus Rahm; Terumasa Tadano; Paul Erhart (Chalmers University of Technology, 2022)
Zeondo dataset for Probing the limits of the phonon quasi-particle picture: The transition from underdamped to overdamped dynamics in CsPbBr3
Keywords: Physical Sciences; Fysik